Architecture and sacrament : a critical theory - Wang, David, 1954- (New York : Routledge, 2020)
"David Wang's Architecture and Sacrament considers contemporary architecture theory from a Christian theological perspective. Wang explains the social and cultural reasons why the theological literature tends to be separate from current literature in architecture theory. This book bridges the divide by showing, for example, how the loss of sacramental outlooks, which guided centuries of art and architecture in the West, can shed light on the plight of "big box stores," the environmental crisis and the loss of a sense of community. The book critiques the materialist basis of current architectural theory, subsumed largely under the banner of critical theory, and calls for a return to a metaphysics building, thinking and dwelling that largely animated the production of Western culture from Greco-Roman times to the Modernist era. This book on how European ideas inform architectural theory compliments Wang's previous book, A Philosophy of Chinese Architecture: Past, Present, Future and will appeal to Architecture students and academics"--
Gardens as Narrated Nature -- Complex Authenticity -- Architecture in Rhythm with History -- Notes -- Bibliography -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- Philosophy; Architecture and religion; ARCHITECTURE / General; ARCHITECTURE / Criticism; PHILOSOPHY / Religious